Hexagon Fraud Analysis in Fraudulent Financial Reporting Detection: With the Audit Committee as a Moderating Variable - Wuku Astuti; Bhenu Artha; Ratri Paramitalaksmi (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
This study analyzes the effectiveness of the Fraud Hexagon Theory in detecting fraudulent financial reporting in state-owned banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. It also evaluates the accuracy of the Beneish M-Score model and the moderating role of the audit committee in this relationship. A quantitative approach is used, with multiple regression and moderation regression analysis of secondary data from annual financial reports. The study focuses on six factors of the Fraud Hexagon Theory: pressure, opportunity, rationalization, capability, arrogance, and collusion. Results show that the nature of the industry significantly influences fraudulent financial reporting, while factors like external pressure, auditor switching, CEO narcissism, and multiple board positions did not. The audit committee moderated the relationship between industry nature, CEO narcissism, and multiple board positions with financial fraud, but had no effect on other factors. These findings emphasize the importance of strong internal controls and governance in the banking sector.